PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN KEPEMUDAAN DAN OLAH RAGA KABUPATEN BADUNG - Ni Made Martini; A. A. Ketut Sri Asih; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2022)
In addition to work motivation, the work environment must be also be considered, a good and conducive work environment will create a comfaortabel working atmosphere. The purposes of this study is to determine the independent variables that have a dominant influence on the performance of Civil Servants at Dinas Pendidikan Kepemudaan dan Olah Raga Kabupaten Badung. The sampling technique used is the cencus technique. The data analysis tool used is multiple linear regression analysis with application (SPSS) version 16.0.the regression equation of this study is Y = 4.107 + 0.568X1 + 1.125X2. The magnitude of the influence of work motivation and work environment on employee performance at Dinas Pendidikan Kepemudaan dan Olah Raga Kabupaten Badung can be seen from the R square value of 0.453. this means that 45,3% of employee performance variables can be explained by work motivation and work environment variables, while the remaining 54,7% is explained by other variables outside this study, 4). The variables that has the most dominant influence is work motivation variables. Judging from the value of the work motivation beta coefficient which is worth 0.405, it is greater than the work environment beta coefficient which is worth 0.404.